Functional Identification of Corynespora cassiicola-Responsive miRNAs and Their Targets in Cucumber - Wang, Xiangyu; Yu, Guangchao; Zhao, Junyue; Cui, Na; Yu, Yang; Fan, Haiyan (Frontiers in Plant Science, 2019)
Target leaf spot (TLS), which is caused by Corynespora cassiicola (C. cassiicola), is one of the most important diseases in cucumber (Cucumis sativus L.). Our previous research identified several C. cassiicola-responsive miRNAs in cucumber by high-throughput sequencing, including two known miRNAs and two novel miRNAs. The target genes of these miRNAs were related to secondary metabolism. In this study, we verified the interaction between these miRNAs and target genes by histochemical staining and fluorescence quantitative assays of GUS. We transiently expressed the candidate miRNAs and target genes in cucumber cotyledons to investigate the resistance to C. cassiicola. Transient expression of miR164d, miR396b, Novel-miR1 and Novel-miR7 in cucumber resulted in decreased resistance to C. cassiicola, while transient expression of NAC (inhibited by miR164d), APE (inhibited by miR396b), 4CL (inhibited by Novel-miR1) and PAL (inhibited by Novel-miR7) led to enhanced resistance to C. cassiicola. In addition, overexpression of 4CL and PAL downregulated lignin synthesis, and overexpression of Novel-miR1 and Novel-miR7 also downregulated lignin synthesis, indicating that the regulation of 4CL and PAL by Novel-miR1 and Novel-miR7 could affect lignin content. The tobacco rattle virus (TRV) induced short tandem target mimic (STTM)-miRNA silencing vector was successfully constructed, and target miRNAs were successfully silenced. The identification of disease resistance and lignin content showed that silencing candidate miRNAs could improve cucumber resistance to C. cassiicola.